Systematic Literature Review on Eco-literacy Learning in the Lower Grades of Elementary School - Utari, Rahmania (Jurnal Prima Edukasia, 2025)
This study highlights the previous studies of eco-literacy learning in the lower grades of elementary school (grades 1-3) using a Systematic Literature Review (SLR). The data was obtained through Google Scholar, Garuda, and Science Direct. The data analysis protocol was the PSALSAR framework paired with the PRISMA protocol. The literature sources were derived from Google Scholar (644), Garuda (10), and Science Direct (65). Of the 719 literature sources, six met the inclusion criteria. The findings of the analysis were divided into three aspects: (1) the content of eco-literacy learning, (2) the methods of eco-literacy learning, and (3) the media of eco-literacy learning. This SLR study identified a research gap for future study and practical implications. For future study, key areas include researching its impact on children's cognitive and emotional development and investigating how schools manage eco-literacy resources using anthropological approaches. It is also suggested that researchers look into societal practices that influence students' environmental behaviors, teachers' science literacy, and the development of environmental education curricula. Additionally, R&D in collaborative strategies for developing eco-literacy content targeted to early-grade learners is highly suggested. The development of particular assessment methods for eco-literacy outcomes is also required. As practical implications, improving teachers' STEM abilities and organizing suitable outdoor learning areas are critical for effective eco-literacy teaching.